2022
DOI: 10.3389/fphar.2022.945836
|View full text |Cite
|
Sign up to set email alerts
|

Intrapallidal injection of cannabidiol or a selective GPR55 antagonist decreases motor asymmetry and improves fine motor skills in hemiparkinsonian rats

Abstract: Cannabidiol (CBD) presents antiparkinsonian properties and neuromodulatory effects, possibly due to the pleiotropic activity caused at multiple molecular targets. Recently, the GPR55 receptor has emerged as a molecular target of CBD. Interestingly, GPR55 mRNA is expressed in the external globus pallidus (GPe) and striatum, hence, it has been suggested that its activity is linked to motor dysfunction in Parkinson’s disease (PD). The present study aimed to evaluate the effect of the intrapallidal injection of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…In addition to AD, GPR55 has been implicated in PD. Recent studies have shown high expression of GPR55 in the striatum and in the external globus pallidus, indicating a potential link between GPR55 activity and motor dysfunction in PD ( Patricio et al, 2022 ; Wong et al, 2023 ). GPR55 and CB1 heteromers have also shown significant neuroprotection against parkinsonism-inducing toxins, as in AD ( Cooray et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to AD, GPR55 has been implicated in PD. Recent studies have shown high expression of GPR55 in the striatum and in the external globus pallidus, indicating a potential link between GPR55 activity and motor dysfunction in PD ( Patricio et al, 2022 ; Wong et al, 2023 ). GPR55 and CB1 heteromers have also shown significant neuroprotection against parkinsonism-inducing toxins, as in AD ( Cooray et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%